Penguatan Nilai-nilai Keislaman Melalui Strategi Dakwah Edukatif di Sekolah Dasar Negeri 1 Bendogerit Kota Blitar - Rohman, Miftakhul; Muttaqin, Asyharul; Najib, Fikri Ainun; Rusydi, Shania Sanra; Arifin, Achmad Midanul (Universitas Islam Internasional Darullughah Wadda'wah, 2025)
Strengthening Islamic values in elementary schools is an urgent necessity to build students’ religious character from an early age. This community service program was implemented at SDN 1 Bendogerit, Blitar City, focusing on the application of systematic, contextual, and sustainable educational da’wah strategies. The method employed was Participatory Action Research (PAR), which actively involved teachers, students, and the surrounding community through the stages of planning, action, observation, and reflection. The activities included Islamic education teacher training, the development of daily worship habituation, the strengthening of Qur’anic literacy, the optimization of worship facilities, and the organization of religious competitions to increase students’ motivation. The results indicate an increase in students’ participation in religious activities, teachers’ skills in managing worship evaluation, and the formation of a more vibrant religious school culture. Thus, participatory-based educational da’wah strategies proved effective in strengthening Islamic values and fostering the religious character of elementary school students.